2016
DOI: 10.1136/jech-2015-206346
|View full text |Cite
|
Sign up to set email alerts
|

Stunting risk of orphans by caregiver and living arrangement in low-income and middle-income countries

Abstract: Early orphanhood constitutes a major risk for children's physical development in LMICs. However, the results suggest that the adverse effects of a parental loss can be mitigated if appropriate support is provided, indicating the potential benefits of the surviving parents staying with their children. The benefits of targeted social policies aimed at single fathers and grandparents supporting orphans may be significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Thus, we are only able to speculate on the results. While orphans are vulnerable to malnutrition, studies have found mixed results on this topic, and it appears the adverse effects of a parental loss may be mitigated if the appropriate resources and support are provided for the child [23, 55]. Child outcomes may also depend on who is ultimately responsible for the orphan’s care [56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we are only able to speculate on the results. While orphans are vulnerable to malnutrition, studies have found mixed results on this topic, and it appears the adverse effects of a parental loss may be mitigated if the appropriate resources and support are provided for the child [23, 55]. Child outcomes may also depend on who is ultimately responsible for the orphan’s care [56].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this literature search, only one study was identified that performed a formal meta-analysis on the association between maternal depression and childhood stunting 13. Since this was the only meta-analysis, studies that were based on analysis of Demographic and Health Survey (DHS) data across a broad range of low/middle-income countries were used for other psychosocial variables, including low maternal education,14 IPV15 and orphanhood 16. For other psychosocial risk factors that did not have a meta-analysis or DHS data across a number of low/middle-income countries, including child abuse, parental use of alcohol and parental substance abuse, insufficient information was available on exposure prevalence to include them in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Living conditions in childhood have profound short- and long-term effects on mental and physical development, even on future marriage [ 9 ]. Current studies on the effects of living arrangements on health mainly focus on children with divorced parents, or who are orphaned, children of political refugees, disabled children, and children in boarding schools [ 10 , 11 , 12 , 13 , 14 , 15 ]. Studies on migrant students mainly focus on the children who are left behind and/or comparisons with local children [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%